THE ATTRACTION AND DEVELOPMENT OF ERGENDANG CAVE HOT SPRINGS IN PENUNGKIREN VILLAGE, STM HILIR DISTRICT, DELI SERDANG REGENCY - Rosni Rosni; Lathifah Rabbaniyah; Muhammad Arif; Elfayetti Elfayetti (Tunas Geografi, 2022)
This study aims to determine: (1) the tourist attraction of the Ergendang Hot Springs, (2) the facilities and infrastructure of the Ergendang Hot springs tourism, (3) the development efforts made by the government in developing Ergendang Cave Hot Springs tourism. Ergendang Cave Hot Springs, (4) Community development efforts in developing Ergendang Cave Hot Springs tourism. Ergendang Cave Hot Springs includes natural scenery, flora and fauna, historical heritage, culture and activities that are classified as moderate category. Meanwhile, visitors' perceptions of the attractiveness of the Ergendang Cave Hot Springs tourist attraction on natural scenery are in the good category (89%), flora and fauna in good category (88%), historic heritage in the bad category (20%), culture in perception is not good. good (20%), and activities carried out in good perception (90%). (2) Tourist facilities at the Ergendang Cave Hot Springs include: transportation, lodging, restaurants, parking lots, toilets, visitor huts, places of worship, tour guides, promotions and trash cans in the medium category. Tourism infrastructure at Eregendang Cave Hot Springs includes: road network, electricity network, telecommunication network, health services, clean water are classified as good category. (3) The development efforts made by the government in developing the Ergendang Cave Hot Spring tourist attraction are: improving the facilities and infrastructure of the Ergendang Cave Hot Spring tourist attraction, holding FGD (Focus Group Discussion) meetings for all tourism business actors and participating in CHSE (cleanliness) certification. , health, safety, environment sustainability) recommended by the Ministry of Tourism, there is good cooperation and agreement between the Tourism Office and the tourism object manager so that the Ergendang Cave Hot Spring tourist attraction is more developed and attractive so that later many visitors will come to the tourist attraction. Ergendang Cave Hot Springs, carried out promotions carried out by the manager and the Tourism Office so that the Hot Springs tourist attraction is better known by tourists. (4) Development efforts carried out by the surrounding community in developing the Ergendang Cave Hot Spring tourist attraction, namely 90% of the people open a food stall or restaurant business as many as 18 units, and 10% of the people who maintain security around the tourist attraction, namely by keeping the vehicles of the tourists. visitors who come to the Ergendang Cave Hot Spring tourist attraction.Keywords: Attractiveness, Tourist Attraction Development, Visitor Perception